PENGARUH UKURAN PERUSAHAAN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Suciati, Suciati; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTOne of the company objectives which should be achieved through the implementation of financial managementfunctions with care and appropriate regarding that every financial decisions which have been made will affectother financial decisions that later will affect the firm value. This research is aimed to find out the influence offirm size, debt policy and firm size to the firm value of go public paper manufacturing companies which arelisted in Indonesia Stock Exchange. The population is all paper manufacturingh companies which are listed inIndonesia Stock Exchange, the sample collection techniques has been done by using purposive sampling and thesamples are 8 companies, the observation periods are made in 2011-2015 periods. The data is the secondary datahas been done by using financial statement. The data analysis has been done by using multiple linearregressions analysis. The result of the research has been carried out by using model feasibility test shows that themodels are feasible to be used for the following research, and hypothesis test which has been performed by using ttest shows that firm size, debt policy and firm size give significant and positive influence to the firm value of gopublic paper manufacturing companies which are listed in Indonesia Stock Exchange.Keywords: firm size, debt policy, profitability, firm value